HIV risk and behaviour among part-time versus professional FSW: baseline report of an interventional cohort in Burkina Faso. (1st February 2016) - Traore, Isidore T; Hema, Noelie M; Sanon, Anselme; Some, Felicien; Ouedraogo, Djeneba; Some, Roselyne; Niessougou, Josiane; Konate, Issouf; Mayaud, Philippe; Van De Perre, Philippe; Meda, Nicolas; Nagot, Nicolas
Abstract : Objective: To readjust HIV control programmes in Africa, we assessed the factors associated with high-risk behaviours and HIV infection among young female sex workers (FSW) in Burkina Faso. Methods: We carried out a cross-sectional study from September 2009 to September 2010 in Ouagadougou, the capital city. FSW were categorised as professionals and part-time sex workers (PTSW). After a face-to-face questionnaire, blood and urine samples were collected for HIV, HSV-2, genital infections and pregnancy. High-risk behaviour was defined as a recent unprotected sex with either casual clients, regular clients or regular partners. Results: We recruited 609 FSW including 188 (30.9%) professionals. Their median age was 21 years (IQR 19–23), and the prevalence of HIV was 10.3% among professionals and 6.5% among PTSW. Only 3 of 46 HIV-infected women were aware of their status. Overall, 277 (45.6%) women reported high-risk behaviours (41.2% among professionals and 47.5% among PTSW), which were driven mainly by non-systematic condom use with regular partners. In multivariable analysis, PTSW (adjusted OR (AOR)=1.89; 95% CI 1.27 to 2.82) and having a primary (AOR=1.75; 95% CI 1.15 to 2.67) or higher education level (AOR=1.80; 95% CI 1.13 to 2.89) remained associated with high-risk behaviours. HIV infection was associated with older age (AOR=1.44; 95% CI 1.22 to 1.71), with being married/cohabiting (AOR=2.70; 95% CI 1.21 to 6.04) and with Trichomonas vaginalis infection (AOR=9.63; 95% CI 2.93 to 31.59), while history of HIV testing was associated with a decreased risk (AOR=0.18; 95% CI 0.08 to 0.40). Conclusions: This study highlights the need for targeted interventions among young FSW focusing particularly on PTSW, sexual behaviours with regular partners and regular HIV testing.